IMPLEMENTASI PROGRAM MANAJEMEN BKI DALAM MENGATASI MASALAH KESISWAAN DI MTSN PANAMPUANG - Muhammad Hafizh (IAIN Batusangkar, 2016)
The purpose ofthis study to determinethe implementation of management program of the critical BKI, according tothe rules ofthe existing curriculum conceptsin MTsN panampuang with the fact that there are in the fiel das well asstudent achievementas a referencefor teachers in evaluating learning and improve student achievement MTsNpanampuang. Found some cases in which students MTsN Panampuang inhibit the learning process. The results of the interview panel of teachers and community leaders found some problems criterion mild, moderate, and severe that in habit learning objectives, such as sexual immorality, poor discipline and extracurricular school programs are rarely attended by the students. Moral character and the lower its value, and some cases of discipline such as skipping, no school extracurricular programs, as well as the difficulty of assembly of teachers in classroom management problems occur due to the number of student. The conclution is management in the Islamic Counseling MTsN Panampuang been effective because management has reached an ideal standard concept in schooll, but not efficient because it has not reached the goal of shaping the character and resolve student issues. Organizing theim plementation of theI CC in MTsN Panampuang management does not give effect to the number of student problems. Key Words: Implementasi, manajemen BKI, masalah siswa